Reputation: 773
I try to simplify the following equation
f = 1/(2*i) *(E**(i*x)-E**(-i*x))
So I wrote this code:
from sympy import *
from sympy.abc import x
init_printing(use_unicode=False, wrap_line=False, no_global=True)
f = 1/(2*I) *(E**(I*x)-E**(-I*x))
trigsimp(f)
I want to get the result as the sine-function, because
1/(2*I) *(E**(I*x)-E**(-I*x)) = sine(x)
Does anyone know, how to get the results simplified as sine, cos... -function?
Many thanks in advance!
John
Upvotes: 2
Views: 71
Reputation: 19029
f.rewrite(sin)
should do it. This is an example of the rewriting capabilities. Whenever you think something can be rewritten in terms of something else, try this method.
Upvotes: 3